THE AUTOMATIZATION OF SPEAKING SKILLS IN THE PROCESS OF BUILDING AN ACADEMIC ENGLISH PROFESSIONAL COMPETENCE IN SPEAKING OF PROSPECTIVE MARKETERS - Аndriana Onufriv (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2016)
The issue of automatization of speaking skills in the process of building an academic English professional competence in speaking of prospective marketers is highlighted. The essence of an academic English professional competence in speaking of prospective marketers has been analyzed. The structure of an academic English professional competence in speaking of prospective marketers (abilities, skills, knowledge, communicative aptitudes) has been studies. Building of speaking skills is based on the acquisition of declarative and procedural knowledge. The presentation is suggested as a leading tool of building an academic English professional competence in speaking of prospective marketers. The ways of automatization of speaking operations in the process of building an academic English professional competence in speaking of prospective marketers has been grounded. It has been established that automatization of speaking operations in the process of building an academic English professional competence  in speaking of prospective marketers occur by the means of developing phonetic, grammar and lexical speaking skills. The automatization   of speaking skills is reached by performing certain exercises and tasks. These assignments are receptive, reproductive ones (by a criterion of leading kind of speaking); warming, stereotype-situational and variant-situational ones (by a criterion of the stages of developing skills); simulative and communicative ones (by a criterion of communication). The most widespread exercise and tasks for developing speaking skills, defined by a criterion of communication, are   non-communicative, simulative and communicative ones.